2010
DOI: 10.1021/ja1073992
|View full text |Cite
|
Sign up to set email alerts
|

First Principle Kinetic Studies of Zeolite-Catalyzed Methylation Reactions

Abstract: Methylations of ethene, propene, and butene by methanol over the acidic microporous H-ZSM-5 catalyst are studied by means of state of the art computational techniques, to derive Arrhenius plots and rate constants from first principles that can directly be compared with the experimental data. For these key elementary reactions in the methanol to hydrocarbons (MTH) process, direct kinetic data became available only recently [J. Catal.2005, 224, 115-123; J. Catal.2005, 234, 385-400]. At 350 °C, apparent activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
211
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 157 publications
(234 citation statements)
references
References 98 publications
21
211
0
2
Order By: Relevance
“…[6] Consequently, numerous studies focused on the methylation by methanol, dimethyl ether or methoxides of aromatics and alkenes in the framework of the MTO process. [16,17,26,42,44,46,82,83] It should be mentioned that the static approach with finite cluster models as applied in most of these studies has been very successful in reproducing and predicting experimentally measured kinetic data. [16,17] However, a similar approach is not applicable for the study of methylation reactions in the large pore AFI structured H-SSZ-24 as will be demonstrated in this case study.…”
Section: Case Study Ii: Simulating Competing Pathways For Benzene Metmentioning
confidence: 99%
See 1 more Smart Citation
“…[6] Consequently, numerous studies focused on the methylation by methanol, dimethyl ether or methoxides of aromatics and alkenes in the framework of the MTO process. [16,17,26,42,44,46,82,83] It should be mentioned that the static approach with finite cluster models as applied in most of these studies has been very successful in reproducing and predicting experimentally measured kinetic data. [16,17] However, a similar approach is not applicable for the study of methylation reactions in the large pore AFI structured H-SSZ-24 as will be demonstrated in this case study.…”
Section: Case Study Ii: Simulating Competing Pathways For Benzene Metmentioning
confidence: 99%
“…[8,[15][16][17] However, theoretical chemists are still confronted with paramount challenges to thoroughly explain experimental observations. The true challenge lies in linking the model system with experimental or industrial conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In this case bimolecular transition state theory should be applied as outlined in the supporting information. More details are also given by Van Speybroeck et al on the computational procedures for discriminating between intrinsic and apparent reaction kinetics 44 .…”
Section: Reaction Kinetics: Direct Versus Radical Pathwaymentioning
confidence: 99%
“…However, for large chemical systems, such as those encountered in heterogeneous catalysis, where adequate models typically include several hundred atoms, the “chemical accuracy” (4 kJ mol −1 for the energy barriers, one order of magnitude for the pre‐exponential factors) required for useful predictions is not attained. The exponential scaling with the system size of both the electronic structure methods (potential energy surface) and the nuclear motion problem (vibrational partition function) limits the applicable method to density functional theory (DFT) for the potential energy surface and the harmonic approximation for the vibrations 4, 5, 6, 7, 8. Depending on the functional, energy barriers may be in error by 10–20 kJ mol −1 , and the harmonic approximation is most problematic for low‐frequency modes, which are known to make the largest contribution to the partition functions 9…”
mentioning
confidence: 99%
“…A deviation of a factor of ten reflects the experimental uncertainty5, 25 and is considered “accurate”. This is indicated by the gray region in the logarithmic plot of Figure 3.…”
mentioning
confidence: 99%